2017
DOI: 10.3389/fmolb.2017.00071
|View full text |Cite
|
Sign up to set email alerts
|

RNA Binding Protein Regulation and Cross-Talk in the Control of AU-rich mRNA Fate

Abstract: mRNA metabolism is tightly orchestrated by highly-regulated RNA Binding Proteins (RBPs) that determine mRNA fate, thereby influencing multiple cellular functions across biological contexts. Here, we review the interplay between six well-known RBPs (TTP, AUF-1, KSRP, HuR, TIA-1, and TIAR) that recognize AU-rich elements (AREs) at the 3′ untranslated regions of mRNAs, namely ARE-RBPs. Examples of the links between their cross-regulations and modulation of their targets are analyzed during mRNA processing, turnov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
132
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(138 citation statements)
references
References 100 publications
4
132
1
1
Order By: Relevance
“…Herein, we found that circ‐CCND1 could directly bind to HuR to potentiate CCND1 mRNA stability. HuR is a well‐known RNA‐binding protein that prevents mRNA decay via targeting the uridylate‐rich element (ARE, (A/U)UUU(A/U)) on the 3′‐UTR . A wealth of studies have demonstrated that HuR is ubiquitously expressed in eukaryotic organization and frequently elevated in human cancers, including LSCC .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herein, we found that circ‐CCND1 could directly bind to HuR to potentiate CCND1 mRNA stability. HuR is a well‐known RNA‐binding protein that prevents mRNA decay via targeting the uridylate‐rich element (ARE, (A/U)UUU(A/U)) on the 3′‐UTR . A wealth of studies have demonstrated that HuR is ubiquitously expressed in eukaryotic organization and frequently elevated in human cancers, including LSCC .…”
Section: Discussionmentioning
confidence: 99%
“…HuR is a well-known RNA-binding protein that prevents mRNA decay via targeting the uridylate-rich element (ARE, (A/U)UUU(A/U)) on the 3′-UTR. 26 A wealth of studies have demonstrated that HuR is ubiquitously expressed in eukaryotic organization and frequently elevated in human cancers, including LSCC. 27 CCND1 is one of the best-known HuR targets, in which HuR increases the half-life of CCND1 by the ARE motif on CCND1 3′-UTR.…”
Section: Discussionmentioning
confidence: 99%
“…Another well‐characterized ARE‐binding protein is HuR (Grammatikakis, Abdelmohsen, & Gorospe, ; López de Silanes, Zhan, Lal, Yang, & Gorospe, ). HuR is known to affect multiple posttranscriptional processes, including mRNA stability and translation (reviewed in García‐Mauriño et al, ; Grammatikakis et al, ). HuR has been shown to increase the stability of transcripts involved in carcinogenesis, cell proliferation and survival, and oxidative and genotoxic cellular response (Fan et al, ; Y. Li, Estep, & Karginov, ).…”
Section: Deadenylation: Rbps and Micrornasmentioning
confidence: 99%
“…Interactions between RNA-binding proteins (RBPs) and RNA are essential for the control of gene expression by regulating the processes of transcription, trafficking, decay and mRNA translation 17 . In this way, RNA-RBP crosstalk controls cell homeostasis and cell fate.…”
Section: Introductionmentioning
confidence: 99%